Clinical characteristics of antithyroid drug-induced aplastic anemia cases over the past 30 years - Cheng, Ying; Xia, Xin-Yu; Zhang, Wei; Ren, Li; Tian, Chen-Fu; Liu, Dan; Xue, Gang (Frontiers in Endocrinology, 2023)
Objective The authors aimed to investigate the clinical characteristics of antithyroid drug-induced aplastic anemia cases over the past 30 years. Methods The data of patients with antithyroid drug-induced aplastic anemia were retrieved from PubMed and Wanfang Medical Network databases from 1992 to August 2022. The clinical characteristics, such as age distribution, gender tendency, common symptoms, blood cell count, bone marrow features, treatment strategy, and prognosis, were analyzed. Results A total of 17 cases (male:female = 1:16) had been retrieved. Patients’ age ranged from 16 to 74 years (median 50 years). Among them, 82.3% (14/17) of the patients were administered methimazole (MMI), and 78.6% of them had MMI ≥30 mg/day. In addition, 88.2% (15/17) of the patients had sore throat and fever, and 47.1% (8/17) of the patients had hemorrhagic symptoms. Aplastic anemia occurred within 6 months after initiation of the antithyroid therapy in 94.1% of the patients. Agranulocytosis (94.1%) was the most common and earliest blood cell change, and 47.1% of the patients experienced progressive platelet decline during the treatment process. The treatments include timely withdrawal of antithyroid drugs, broad-spectrum antibiotics, granulocyte colony-stimulating factor (G-CSF)/granulocyte-macrophage colony-stimulating factor (GM-CSF), glucocorticoids and other immunosuppressive agents, and supportive treatments such as erythrocyte transfusion and platelet transfusion. Moreover, 70.6% of the patients had complete or near-complete remission within 8 days to 6 weeks. Conclusion Aplastic anemia is a rare and serious adverse reaction of antithyroid drugs, which is more common in women. It usually occurs during early treatment with high-dose antithyroid drugs. Most patients have a good prognosis after timely drug ceasing and appropriate treatment.